Analisis Hubungan Perilaku Merokok dengan Obesitas Sentral Pada Orang Dewasa Sehat di Suradadi Kabupaten Tegal - Agus Susanto; Eva Novita Sari; Ratih Sakti Prastiwi (Universitas Pahlawan, 2021)
Central obesity is influenced by many factors such as changes in age, gender, economic status, life habits including lack of physical activity, low fiber consumption, consumption of simple carbohydrates, consumption of fatty foods, and smoking behavior. Smoking behavior is thought to be a significant factor in forming central obesity in adult males. The purpose of this study was to determine the relationship between smoking behavior and central obesity in healthy adults. Â This study used an analytic observational design with a cross-sectional research design. The research was conducted in Suradadi Village, Suradadi District, Tegal Regency. Sampling was carried out by stratified sampling in November 2020 â€“ January 2021. The sample size was 90 men aged 25-60 years. Data were collected by measuring the waist circumference of the respondents and recording other personal data such as age, occupation, and smoking status. Data processing is done descriptively and cross-tabulation. Testing the relationship between smoking behavior and obesity was carried out using the chi-square statistical test with the help of the SPSS version 22 application. The majority of respondents in this study had a smoking status of 68.9% and did not have central obesity 64.4%. The results of the test of the relationship between smoking status and central obesity got a p-value of 0.813. There is no significant relationship between smoking status and central obesity.